Understanding E-Loyalty In E-Commerce Through the Lens of the Theory of Planned Behavior - Marianus, Vinsensius; Masnita, Yolanda; Kurniawati, Kurniawati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The shift in shopping behavior from face-to-face to online transactions requires e-commerce platforms to improve service quality to maintain customer loyalty. This study aims to examine the effect of e-service quality, e-recovery service quality, and e-trust on e-loyalty, with e-satisfaction as a mediating variable. This quantitative study used a survey method, involving 145 respondents, active e-commerce users in Indonesia, selected through purposive sampling. Data were collected using a Google Forms questionnaire and analyzed using AMOS-based Structural Equation Modeling (SEM). The results showed that e-service quality had a positive and significant effect on e-satisfaction and e-loyalty. Meanwhile, e-recovery service quality did not have a direct impact on e-loyalty, but had a significant indirect effect through e-satisfaction, thus requiring satisfaction as a mediator. Furthermore, e-trust had a positive and significant effect on e-satisfaction. Still, no significant impact on e-loyalty, indicating that customer trust alone is insufficient to create loyalty without satisfaction. Overall, e-satisfaction proved to be a substantial mediator bridging the relationship between the three independent variables and e-loyalty. These findings confirm that improved service quality, faster problem resolution, and a stronger sense of security in digital transactions are key factors in building customer satisfaction and maintaining loyalty on e-commerce platforms.